2020
DOI: 10.1016/j.icarus.2020.113686
|View full text |Cite
|
Sign up to set email alerts
|

A model of the 3-μm hydration band with Exponentially Modified Gaussian (EMG) profiles: Application to hydrated chondrites and asteroids

Abstract: We present here a new method to model the shape of the 3-µm absorption band in the reflectance spectra of meteorites and small bodies. The band is decomposed into several OH/H2O components using Exponentially Modified Gaussian (EMG) profiles, as well as possible organic components using Gaussian profiles when present. We compare this model to polynomial and multiple Gaussian profile fits and show that the EMGs model returns the best rendering of the shape of the band, with significantly lower residuals. We als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Beauregard displays only a weak band as a shoulder of the wide and strong band covering the whole 2800 to 4000 nm range. This latter band is partly due to H 2 O in the crystal structure (around 3100‐3200 nm), and to adsorbed H 2 O (around 2850‐2950 nm) (see eg, 25 ) but hematite [α‐Fe 2 O 3 ] (or hydrohematite, with part of the O replaced by OH, [~α‐Fe 1.83 (OH) 0.5 0 2.5 ]) and goethite [α‐Fe 3+ O(OH)] also strongly contribute around 2930 and 3150 nm, the second band being almost as strong as the first one for goethite, but only present as an extended wing in hematite 26 (Figure 7). The band around 2930 nm is relatively similar in almost all our standard pigments except Pierrerue, which seems to have a stronger band and shifted toward lower wavelength (2890 nm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beauregard displays only a weak band as a shoulder of the wide and strong band covering the whole 2800 to 4000 nm range. This latter band is partly due to H 2 O in the crystal structure (around 3100‐3200 nm), and to adsorbed H 2 O (around 2850‐2950 nm) (see eg, 25 ) but hematite [α‐Fe 2 O 3 ] (or hydrohematite, with part of the O replaced by OH, [~α‐Fe 1.83 (OH) 0.5 0 2.5 ]) and goethite [α‐Fe 3+ O(OH)] also strongly contribute around 2930 and 3150 nm, the second band being almost as strong as the first one for goethite, but only present as an extended wing in hematite 26 (Figure 7). The band around 2930 nm is relatively similar in almost all our standard pigments except Pierrerue, which seems to have a stronger band and shifted toward lower wavelength (2890 nm).…”
Section: Resultsmentioning
confidence: 99%
“…This will need to take into account the substrate, but we have shown that measuring a paint at different places with different thicknesses (including the bare substrate) and also at a couple of very different illumination angles may provide a tool to help separate both contributions. This radiometric method may also provide some quantitative mineralogical information not provided by other techniques, such as structural water, OH… 25 …”
Section: Resultsmentioning
confidence: 99%
“…The spectra of the CI Orgueil, Tagish Lake and CM chondrites are taken from Potin et al (2019) and Potin et al (2020b). The spectra of CO and CV chondrites are taken from Eschrig et al (2020).…”
Section: Methods 21 Reflectance Datasetsmentioning
confidence: 99%
“…Also, the SHADOWS instrument measures bi-directional reflectance spectra unlike most-systems that are biconical. All spectra are accessible through the SSHADE database (www.shade.eu).The spectra of the CI Orgueil, Tagish Lake and CM chondrites are taken from Potin et al ( 2019) and Potin et al (2020b). The spectra of CO and CV chondrites are taken from Eschrig et al (2020).…”
mentioning
confidence: 99%
“…It can make the spectral curves redden and darken, and difficult to identify and interpret (Hapke 2001;Chapman 2004;Han et al 2020). Therefore, many methods for space weathering spectral deconvolution are extensively studied in order to acquire the truth data interpretation (Sunshine & Pieters 1993Gallie et al 2008;Han et al 2020;Potin et al 2020).…”
Section: Introductionsmentioning
confidence: 99%